PEMANFAATAN SABUT KELAPA MENGGUNAKAN MOL SEBAGAI PUPUK ORGANIK CAIR UNTUK PERTUMBUHAN DAN HASIL TERUNG GELATIK (Solanum Melongena L.) - Junaidi Junaidi (Sekolah Tinggi Pariwisata Mataram, 2021)
The research objective was to determine the effect of fermentation time and dose of coconut husk liquid organic fertilizer on the growth and yield of wrench eggplant, both the single effect of fermentation time and the dose of coconut husk liquid organic fertilizer, as well as the combination interaction on the growth and yield of wrench eggplant. This research was conducted in the experimental garden of Madako Tolitoli University, Baolan District, Tolitoli Regency, Central Sulawesi Province. Conducted from May to July 2020. This study used a factorial randomized block design (RBD) consisting of 2 (two) factors. Factor I: Long fermentation which consists of 2 levels; F1: 7 days fermentation, F2: 14 days of fermentation. Second factor: The dosage of coconut husk liquid organic fertilizer which consists of 4 levels; D0: Control, D1: Dose 18 ml / plot, D2: Dose 36 ml / plot, D3: Dose 54 ml / plot. The results showed that the single factor treatment of coconut husk POC dosage at a dose of 18 ml / plot gave better results in the observation parameters of wrench eggplant height and leaf number at 5 and 6 MST. Likewise, the interaction between the combination of fermentation time and the dosage of coconut husk liquid organic fertilizer gave better results in the observed parameters of fruit diameter and weight.